Light-powered self-rolling of a liquid crystal elastomer-based dicycle - Li, Kai; Zhao, Chongfeng; Qiu, Yunlong; Dai, Yuntong (Applied mathematics and mechanics, 2025)
Conventional liquid crystal elastomer (LCE)-based robots are limited by the need for complex controllers and bulky power supplies, restricting their use in micro-robots and soft robots. This paper introduces a novel light-powered dicycle that uses an LCE rod, enabling self-rolling by harvesting energy from the environment. The LCE rod serves as the driving force, with energy being supplied by a line light source. Employing a dynamic LCE model, we calculate the transverse curvature of the LCE rod after deformation, as well as the driving moment generated by the shift in a rod’s center of gravity, which allows the dicycle to roll on its own. Through extensive numerical simulations, we identify the correlations between the angular velocity of the dicycle and the key system parameters, specifically the light intensity, LCE rod length, light penetration depth, overall mass of the dicycle, rolling friction coefficient, and wheel radius. Further, the experimental verification is the same as the theoretical result. This proposed light-powered self-rolling dicycle comes with the benefits of the simple structure, the convenient control, the stationary light source, and the small luminous area of the light source. It not only demonstrates self-sustaining oscillations based on active materials, but also highlights the great potential of light-responsive LCE rods in applications such as robotics, aerospace, healthcare, and automation.